Dynamic event-triggered formation maneuver in cooperative marine surface vehicles control over directed communication networks - Zheng, Yuxin; Zhang, Lei; Huang, Bing; Zhu, Cheng; Su, Yumin (Ocean engineering, 2023)
This article focuses on the dynamic event-triggered formation control problem for multiple marine surface vehicles (MSVs) considering model uncertainties and external disturbances under a unidirectional communication topology. Firstly, a model-parameter-free control strategy is developed to compensate for the adverse effect of parameter uncertainty and time-varying external disturbances by resorting to the sliding mode philosophy and the adaptive law. In contrast to backstepping-based formation control schemes, the proposed control scheme circumvents the complexity explosion, and there is no complex calculation process. Thus, it has a relatively simple structure. After that, to reduce the communication frequency among inter-MSVs, a dynamic event-triggered control (DETC) mechanism is developed. Compared with the existing event-triggered mechanism, the proposed controller ensures fewer triggering instants among vehicles. Finally, theoretical analysis and numerical simulations have shown the effectiveness and superiorities of the proposed methods. •A novel model-parameter-free control strategy is developed to compensate for the adverse effect of parameter uncertainty and time-varying external disturbances.•A dynamic event-triggered mechanism is designed to reduce network traffic while guaranteeing the system's performance and stability.•The proposed methods possess the properties of high robustness and applicability.